Análise do eixo H2S/ CSE/HIF-2α na doença do refluxo gastresofagico: avaliação da inflamação e da integridade da mucosa esofágica - Nogueira, Kerolayne de Melo (2023)
Gastroesophageal Reflux Disease (GERD) is a chronic clinical manifestation. Its development is multifactorial, with inflammatory responses mediated by cytokines. Recent studies have shown that H2S modulation has a protective effect with the reduction of cytokines involved in the pathophysiology of GERD and that it can act on hypoxia via HIF2-α. Therefore, the aim of the present study was to evaluate the H2S/CSE/HIF-2α pathway, associated with esophageal inflammation and changes in mucosal integrity in gastroesophageal reflux disease. For this, GERD was surgically induced in Swiss mice using a modification of the method described by Silva et al., 2017. The animals were divided into the following groups: Sham, Operated, D-Cis, L-cys, CSE Antagonist + L- cysteine; CBS antagonist + L-cysteine. The animals were euthanized 3 days after the start of the experiment. The esophagus was collected for evaluation of wet weight, myeloperoxidase (MPO), keratinocyte-derived chemokine (KC), transepithelial electrical resistance (TER), basal fluorescein permeability, CSE and HIF-2α expression in the esophageal mucosa. The research was also carried out with biopsies of patients (humans) with GERD that were collected at the Hospital Universitário Walter Cantídio, which had the erosive or non-erosive form. From the methods used, the results demonstrated that the pharmacological modulation of the L-cysteine/CSE/H2S pathway prevented esophageal inflammation and the impairment of the integrity of the esophageal mucosa associated with the GERD model. The GERD model showed overexpression of CSE and HIF2-α, which were reversed by treatment with L-cysteine. There was a significant difference in the ERT of patients with erosion when compared to patients with non-erosive esophagitis. Furthermore, there was a significant increase in the levels of pro-inflammatory cytokines and in the expression of CSE and HIF2-α when compared to patients without erosion. Through the results obtained in that study, it can be concluded that the modulation of the L-cysteine/CSE/H2S pathway has a critical role in esophageal inflammation and in the impairment of the mucosal barrier in the GERD model and also in patients with GERD. together, it can be inferred that H2S has a protective effect on gastroesophageal reflux, by downregulating HIF-2 α.